Lovins on the soft path an energy future with a future - Lovins, L. Hunter, 1950-; Lovins, Amory B., 1947-; Lynde, George C.; Prager, Marjorie; Essex County Ecology Center Films; Envision Corporation (Oley, PA : Bullfrog Films, 1982)
Energy analysts Amory and Hunter Lovins explain why they believe that the only long-term solution to the energy crisis lies in using energy efficiently and in adopting renewable energy sources. Uses animation and charts to present complex information in an understandable manner
Copy in DVD Format
Camera, Kevin Burke
Narrator: Robert J. Lurtsema
VHS Format
Keywords: Energy conservation; Renewable energy sources